Outside CEOs, board control and the financing policy of small privately held family firms. Issue 1 (March 2017) - Lardon, Andy; Deloof, Marc; Jorissen, Ann
Abstract: We investigate how the presence of an outside CEO is related to the financing policy of privately held family firms, taking into account the degree of family control via the board of directors. For a sample of 367 Belgian firms we find that family firms with an outside CEO have a lower leverage, although they take more entrepreneurial risk. The negative relation between the presence of an outside CEO and leverage is more pronounced for long-term debt than for short-term debt. Family control via the board of directors reduces the effect of an outside CEO on entrepreneurial risk and leverage.